Emotions, Thoughts, Words - Kochunts, Karine (Armenian Folia Anglistika, 2020)
The subject of the present research is the subtle and intricate interconnection of human emotions, thoughts and words. As we know, human cognition is the ultimate form of reflecting the objective reality. Emotions reflect not the objective items and phenomena of the real world, but some subjective relationships in which these items exist. Thoughts and feelings in the model of the interaction of our consciousness with the world are the two means of its perception. Reflection has got two spheres: an intellectual and an affective, and the interaction of these two means that the rational and the emotional in the consciousness and thinking is manifested in the fact that man can emotionally experience what he/she reflects.
Keywords: emotion; sensitive understanding; emotive; emotive seme; emotive meaning; loaded language